Acetylcholine and an acetylcholinesterase inhibitor neostigmine can aggravate tularemia progress in BALB/c mice - Pohanka, Miroslav; Pavlis, Oto; Svobodova, Hana; Pikula, Jiri (Interdisciplinary toxicology, 2012)
The present experiment was aimed at assessing the application of neostigmine, an acetylcholinesterase (AChE) pseudo-irreversible inhibitor with poor penetration through the hematoencephalitic barrier, and the neurotransmitter acetylcholine (ACh). The experiment was done to evaluate their ability to modulate an infectious disease: tularemia. Mice infected with Franciselle tularensis and exposed to either ACh or neostigmine had a higher mortality and spleen bacterial burden when compared to infected mice exposed to saline solution only. The activated cholinergic anti-inflammatory pathway suppressed pathways necessary for tularemia resolution. Administration of AChE inhibitors to the individuals suffering from tularemia is contra-indicatory. Drugs based on AChE inhibition should be restricted when tularemia or disease with a similar pathogenesis is suspected.
Keywords: parasympathicus; cholinergic system; cholinergic anti-inflammatory pathway; intracellular pathogen; Francisella tularensis; immunomodulation